Family characteristics, sexual practices, and pregnancy among female adolescents in Tondo, Manila - Gayares, Danielle A. (Animo Repository, 2017)
The Philippines number of births by adolescent mothers present as an anomaly to global and regional trends: it is steadily increasing for the last three decades. Previously considered as non-vulnerable, urban residents are new emerging groups in the phenomenon. Changes in family dynamics brought about by labor migration and progressing concepts on ideal family set-up are widely considered to have a social cost to the family, especially young female children. This study involved the survey of 100 women in selected barangays in Tondo, Manila to determine the relationship between family characteristics, sexual practices, and pregnancy during their adolescent years. Among the family characteristics tested, living with the biological father is linked with age of sexual debut. In turn, age of sexual debut is linked with age of first pregnancy and number of adolescent pregnancies. Meanwhile, being raised by a grandmother and having a sister with history of adolescent pregnancy are linked with number of sexual partners during adolescence.